Potensi Makanan Tradisional Nasi Cengklik Sebagai Daya Tarik Wisata Gastronomi - Purnaningsih, Sri; Hamidah, Siti; Nugraheni, Mutiara (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2024)
This study aims to analyze the traditional culinary dish, Nasi Cengklik, as a gastronomic potential in Cengklik Reservoir, Boyolali, Central Java. Nasi Cengklik is a traditional dish that has not been previously researched, making it inherently attractive for study. The research methodology used is the product development research method with the 4D steps, namely define, design, develop, and disseminate, coupled with a qualitative descriptive method based on theoretical foundations. Data collection methods involve primary data through observations, interviews with tourism managers and culinary entrepreneurs, as well as secondary data from journals and documents related to tourism and culinary arts. Data analysis in this study utilizes descriptive analysis of the collected data, followed by drawing conclusions. The research findings indicate that Nasi Cengklik is a traditional culinary delight that can support the existence of Cengklik Reservoir. This is evident through its uniqueness, authenticity, and diversity stemming from traditional cooking methods and distinctive flavors achieved by using local ingredients, such as brown rice, genjer leaf midribs, and wader pari served with banana leaves and rattan plates, adding a classic touch and cultural value to the dish.